Aurora kinase A mediates c‐Myc's oncogenic effects in hepatocellular carcinoma. Issue 11 (4th October 2014) - Lu, Longfeng; Han, Han; Tian, Yuan; Li, Wenjuan; Zhang, Jinxiang; Feng, Maohui; Li, Youjun
<x xml:space="preserve">Abstract</x> Dysregulation of c‐Myc (Myc) has been shown to contribute to progression of hepatocellular carcinoma, however, the detailed molecular mechanism remains poorly understood. Here, we report that Myc binds to the Aurora kinase A (Aurka) promoter and induces expression of Aurka in HCC cells. Increased expression of Aurka correlates with that of Myc in HCC. Nuclear accumulation of Aurka was confirmed by subcellular protein fractionation and immunoblot experiments in HCC cells. Myc inhibition decreases the nuclear accumulation of Aurka in HCC cells. Also Aurka accumulating in the nucleus up‐regulates Myc transcription by binding the Myc promoter containing the highly conserved CCCTCCCCA in the NHE region of the CpG islands. Inhibition of Myc or Aurka diminishes the malignant phenotypes of HCC cells by down‐regulating some common target genes. Also Aurka and Myc mediates the effects of each other, at least partially, on proliferation, anchorage‐independent soft agar growth, and ATP production. Blocking Aurka in an orthotopic model significantly impairs tumor growth in mice. These results identify a Myc‐Aurka feedback loop in which Myc and Aurka regulate expression of each other at the transcriptional level and both play an important role in hepatocarcinogenesis. © 2014 Wiley Periodicals, Inc.